MANAJEMEN PERENCANAAN STRATEGIS SEKOLAH DASAR Studi Kasus di SD Aisyiyah Muhammadiyah 3 Makassar - Ni’ma Wati; Suardi; Idawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Strategic planning is a fundamental component of elementary school management to ensure sustainable educational quality. This study aims to analyze strategic planning practices at SD Aisyiyah Muhammadiyah 3, focusing on the formulation of the school’s vision, mission, and goals; the preparation of the School Development Plan (RPS), School Work Plan (RKS), and School Activity and Budget Plan (RKAS); as well as the implementation of performance indicators and the Internal Quality Assurance System (SPMI). This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, document analysis, and questionnaires. The findings indicate that the school’s strategic planning has been implemented in a participatory manner involving the foundation, school committee, teachers, and parents. School programs are strongly aligned with the formulated vision and mission, particularly in strengthening Islamic character education and student potential development. However, the implementation of SPMI remains at an early stage, and school performance indicators are largely based on external standards. This study recommends strengthening SPMI, developing contextual performance indicators, and implementing data-based planning to improve the quality of elementary education.